Computational Exploration of the Li-Electrode|Electrolyte Interface in the Presence of a Nanometer Thick Solid-Electrolyte Interphase Layer - Li, Yunsong; Leung, Kevin; Qi, Yue (Accounts of chemical research, 2016)
A nanometer thick passivation layer will spontaneously form on Li-metal in battery applications due to electrolyte reduction reactions. This passivation layer in rechargeable batteries must have “selective” transport properties: blocking electrons from attacking the electrolytes, while allowing Li+ ion to pass through so the electrochemical reactions can continue. The classical description of the electrochemical reaction, Li+ + e → Li0, occurring at the Li-metal|electrolyte interface is now complicated by the passivation layer and will reply on the coupling of electronic and ionic degrees of freedom in the layer. This passivation layer is called “solid electrolyte interphase (SEI)” and is considered as “the most important but the least understood in rechargeable Li-ion batteries,” partly due to the lack of understanding of its structure–property relationship. Predictive modeling, starting from the ab initio level, becomes an important tool to understand the nanoscale processes and materials properties governing the interfacial charge transfer reaction at the Li-metal|SEI|electrolyte interface. Here, we demonstrate pristine Li-metal surfaces indeed dissolve in organic carbonate electrolytes without the SEI layer. Based on joint modeling and experimental results, we point out that the well-known two-layer structure of SEI also exhibits two different Li+ ion transport mechanisms. The SEI has a porous (organic) outer layer permeable to both Li+ and anions (dissolved in electrolyte), and a dense (inorganic) inner layer facilitate only Li+ transport. This two-layer/two-mechanism diffusion model suggests only the dense inorganic layer is effective at protecting Li-metal in electrolytes. This model suggests a strategy to deconvolute the structure–property relationships of the SEI by analyzing an idealized SEI composed of major components, such as Li2CO3, LiF, Li2O, and their mixtures. After sorting out the Li+ ion diffusion carriers and their diffusion pathways, we design methods to accelerate the Li+ ion conductivity by doping and by using heterogonous structure designs. We will predict the electron tunneling barriers and connect them with measurable first cycle irreversible capacity loss. Finally, we note that the SEI not only affects Li+ and e – transport, but it can also impose a potential drop near the Li-metal|SEI interface. Our challenge is to fully describe the electrochemical reactions at the Li-metal|SEI|electrolyte interface. This will be the subject of ongoing efforts.